Liability for latent damage (Thomas Telford Telford, 1991)
This title is a l leaflet which is part of the series of guidance notes from ICE Legal Affairs Panel written to clarify contentious issues affecting the civil engineer. Some of the issues covered in the booklet include the basis of liability liability in contract, liability in tort and liability under statute.